Learning to Account for Good Abandonment in Search Success Metrics - Khabsa, Madian; Crook, Aidan C.; Awadallah, Ahmed; Zitouni, Imed; Anastasakos, Tasos; Williams, Kyle (Interactional Conference on Information and Knowledge Management (CIKM '16), 2016)
Abandonment in web search has been widely used as a proxy to measure user satisfaction. Initially it was considered a signal of dissatisfaction, however with search engines moving towards providing answer-like results, a new category of abandonment was introduced and referred to as Good Abandonment. Predicting good abandonment is a hard problem and it was the subject of several previous studies. All those studies have focused, though, on predicting good abandonment in offline settings using manually labeled data. Thus, it remained a challenge how to have an online metric that accounts for good abandonment. In this work we describe how a search success metric can be augmented to account for good abandonment sessions using a machine learned metric that depends on user's viewport information. We use real user traffic from millions of users to evaluate the proposed metric in an A/B experiment. We show that taking good abandonment into consideration has a significant effect on the overall performance of the online metric.